Implementasi Model Prototyping Dalam Perancangan Sistem Informasi Desa - Supiyandi Supiyandi; Chairul Rizal; Barany Fachri (Resolusi : Rekayasa Teknik Informatika dan Informasi, 2023)
For the purpose of gathering data, observations, interviews, and literature reviews were made. The administration level of access is provided by the design of the village information system, and it includes entity relationship diagrams in the database design in addition to analysis, design, coding, and testing services. The availability of a website-based village information system would make it easier for village officials to process village information data and provide information on village government in Lau Gumba Village more effectively and efficiently. Additionally, researchers introduced components of widely informed activities. As a way of information in web development in Lau Gumba Village utilizing the prototype approach in design, the village information system is outfitted with a web-based display so that users can modify the content in the system. North Sumatra is home to the settlement of Lau Gumba. As a hamlet, there is still information that has not been widely disseminated by electronic means of communication. Designing an information system is important as a result. The use of technology has transformed how people obtain information and data. In both public and private institutions, technology helps organize management systems and labor processes. The usage of the Village Information System is one of the uses of information technology in village life (SID). This village information system was created utilizing the prototyping process, which is common for creating village information systems. As a result, a prototype model for a website-based savings and loan application was created.